2009
DOI: 10.1007/s00345-009-0498-6
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of EZH2 expression in human spermatogenic disorders and testicular germ cell tumors

Abstract: Our data strongly suggest that in TGCT EZH2 does not exert its often assumed oncogenic properties during malignant transformation and progression. High EZH2 levels in normal testicular tissue and the inverse association of its expression levels with the severity of spermatogenic failure point to its potential value as a molecular marker for spermatogenic defects and may indicate an important physiological role of EZH2 during intact spermatogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…This is due to lower levels of DNA methylation and of histone methylation (H3K9me2 and H3K27me3; Almstrup et al, 2010). This is consistent with a lower expression of the gene encoding for the EZH2 in the TGCC compared to normal testis tissues (Hinz et al, 2010). This suggests that in TGCC EZH2 does not exert its often assumed oncogenic properties during malignant transformation and progression.…”
Section: Epigenetic and Testicular Cancerssupporting
confidence: 82%
“…This is due to lower levels of DNA methylation and of histone methylation (H3K9me2 and H3K27me3; Almstrup et al, 2010). This is consistent with a lower expression of the gene encoding for the EZH2 in the TGCC compared to normal testis tissues (Hinz et al, 2010). This suggests that in TGCC EZH2 does not exert its often assumed oncogenic properties during malignant transformation and progression.…”
Section: Epigenetic and Testicular Cancerssupporting
confidence: 82%
“…Quantitative meiotic splicing regulation also takes place in other genes implicated in key roles in germ cell development. The Ezh2 gene encodes an important chromatin modifier that can affect development (80) and might play an important role in normal fertility (81,82). A mutually exclusive exon is selected in the Ate1 gene, and the meiotic Ate1 mRNA isoform is the major mRNA made from this gene in the mouse testis (Supplementary File S1).…”
Section: Discussionmentioning
confidence: 99%
“…The only reported exception of downregulation of EZH2 in human carcinoma was observed in testicular germ cell tumors, in which a decreased EZH2 mRNA was detected in seminoma and nonseminoma tumor compared to normal testicular parenchyma. 95 Using quantitative real-time polymerase chain reaction (qRT-PCR) or immunohistochemistry, only 3 previous studies [61][62][63] have reported a similar increase of EZH2 in RCC. Table 5 shows a detailed summary of all published studies reporting the association of EZH2 at the protein level with the tumor's clinicopathologic characteristics and outcome in carcinomas of different organs.…”
mentioning
confidence: 99%